2002
DOI: 10.1002/glia.10063
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell caveolin‐1 expression increases during myelination and decreases after axotomy

Abstract: The caveolins are a family of related proteins that form the structural framework of caveolae. They have been implicated in the regulation of signal transduction, cell cycle control, and cellular transport processes, particularly cholesterol trafficking. Caveolin-1 is expressed by a variety of cell types, including Schwann cells, although its expression is greatest in differentiated cell types, such as endothelial cells and adipocytes. In the present work, we characterize caveolin-1 expression both during rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 64 publications
2
41
0
1
Order By: Relevance
“…It has been noted previously that the abundance of a large number of mRNAs expressed in Schwann cells increases only late after myelination (e.g., genes involved in storage lipid metabolism) (Verheijen et al, 2003). The corresponding cluster (Late-UP) includes fatty acid synthase (Fasn) (Salles et al, 2002), Cdh1, Ndrg1 (Berger et al, 2004), dystrophin-related protein 2 (Drp2), caveolin-1 (Cav1) (Mikol et al, 2002), and the actin filament-severing gelsolin (Gsn) (Gonçalves et al, 2010). There is also a large cluster of mRNAs of which the abundance significantly decreases after the early stages ("descending"), though the protein product has been identified by MS in mature myelin.…”
Section: Abundance Profiles Of Mrnas Encoding Pns Myelin Proteinsmentioning
confidence: 99%
“…It has been noted previously that the abundance of a large number of mRNAs expressed in Schwann cells increases only late after myelination (e.g., genes involved in storage lipid metabolism) (Verheijen et al, 2003). The corresponding cluster (Late-UP) includes fatty acid synthase (Fasn) (Salles et al, 2002), Cdh1, Ndrg1 (Berger et al, 2004), dystrophin-related protein 2 (Drp2), caveolin-1 (Cav1) (Mikol et al, 2002), and the actin filament-severing gelsolin (Gsn) (Gonçalves et al, 2010). There is also a large cluster of mRNAs of which the abundance significantly decreases after the early stages ("descending"), though the protein product has been identified by MS in mature myelin.…”
Section: Abundance Profiles Of Mrnas Encoding Pns Myelin Proteinsmentioning
confidence: 99%
“…We have demonstrated that RAGE promotes S100B secretion from SC by recruiting S100B in secretory vesicles and that RAGE triggering induces the phosphorylation of caveolin 1 (cav-1), which is necessary for RAGE-promoted S100B secretion and morphological changes in SCs (Perrone et al, 2008). It has been suggested that cav-1 has a function in myelinating SCs (Mikol et al, 2002) and diabetic neuropathy is exacerbated in Cav1 -/-mice (Donato et al, 2009). Cav-1 is associated with membrane microdomains that are enriched in cholesterol and sphingolipids and defined as lipid rafts (Cohen et al, 2004;Perrone and Zurzolo, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol comprises about 25% of myelin lipid, and SCs derive all their cholesterol for myelination from de novo synthesis (Jurevics and Morell, 1995). Facilitating cholesterol transport would be consistent with the presence of a cytosolic pool of Cav-1 in SCs (Mikol et al, 1999) and increased Cav-1 expression during periods of active myelination in vivo (Mikol et al, 2002). Furthermore, Cav-1 also strongly colocalizes with staining for myelin basic protein, a marker of myelinating SCs, suggesting a tight association of Cav-1 with myelination ( Fig.…”
Section: Caveolin-1 In Schwann Cell Function and Dpnmentioning
confidence: 77%
“…Similarly, axotomy also strongly down-regulated the expression of Cav-1 in SCs but had little effect on Cav-1 expression in blood vessels or the perineurium (Mikol et al, 2002). These observations suggest that the effect of diabetes on Cav-1 expression may have a very cell-specific basis.…”
Section: Altered Cav-1 Expression In Diabetic Nervementioning
confidence: 79%
See 1 more Smart Citation